Luminescent properties of MeMoO4 (Me=Ca, Sr, Zn, Li2) single crystals - Savon, A.; Spassky, D. (Видавництво Львівської політехніки, 2012)
The luminescent properties of MeMoO4 (Me=Ca, Sr, Zn, Li2) single crystals were studied. All the results are discussed in view of applying these scintillating materials in cryogenic environment.
Keywords: molybdates; luminescence; scintillating bolometer; energy transfer mechanisms